Tuhan dan Cinta Perspektif Neo-Vedanta - Resti Telasih, Ni Putu (PANGKAJA: JURNAL AGAMA HINDU, 2019)
In life, love becomes very important. Love is likened to the flowers that bloom in the garden of life. Knowing love makes people happy. There is no sadness, hatred and anger if humans love each other. Loving also has a huge impact, especially in human character. A loving person will easily sacrifice himself for something he loves. This is called altruistic teaching, selfless sacrifice. But can love for humans defeat love for God? Can humans love God completely? This question can be answered through the Neo-Vedanta Philosophy developed by Swami Vivekananda. Vivekananda says that love has no limits. It can be said that  God’s  form in life is love. The more  a person is able to feel love and love everything around him, the more his consciousness will develop. Love and consciousness are one of two sides of the same coin. Surely there is nothing wrong in loving, and be the Lovers who find God in love, so there is no doubt in your life to always spread love.